Temperature-dependent Wsm1 and Wsm2 gene-specific blockage of viral long-distance transport provides resistance to wheat streak mosaic virus and triticum mosaic virus in Wheat - Tatineni, S.; Wosula, Everlyne N.; Bartels, M.; Hein, G.L.; Graybosch, R.A. (Scientific Societies, 2016)
Wheat streak mosaic virus (WSMV) and Triticum mosaic virus (TriMV) are economically important viral pathogens of wheat. Wheat cvs. Mace, carrying the Wsm1 gene, is resistant to WSMV and TriMV, and Snowmass, with Wsm2, is resistant to WSMV. Viral resistance in both cultivars is temperature sensitive and is effective at 18°C or below but not at higher temperatures. The underlying mechanisms of viral resistance of Wsm1 and Wsm2, nonallelic single dominant genes, are not known. In this study, we found that fluorescent protein–tagged WSMV and TriMV elicited foci that were approximately similar in number and size at 18 and 24°C, on inoculated leaves of resistant and susceptible wheat cultivars. These data suggest that resistant wheat cultivars at 18°C facilitated efficient cell-to-cell movement. Additionally, WSMV and TriMV efficiently replicated in inoculated leaves of resistant wheat cultivars at 18°C but failed to establish systemic infection, suggesting that Wsm1- and Wsm2-mediated resistance debilitated viral long-distance transport. Furthermore, we found that neither virus was able to enter the leaf sheaths of inoculated leaves or crowns of resistant wheat cultivars at 18°C but both were able to do so at 24°C. Thus, wheat cvs. Mace and Snowmass provide resistance at the long-distance movement stage by specifically blocking virus entry into the vasculature. Taken together, these data suggest that both Wsm1 and Wsm2 genes similarly confer virus resistance by temperature-dependent impairment of viral long-distance movement.